Results of a Stand-Alone PCI Program at Schneider Regional Medical Center - Vinall, Maria (MD Conference Express, 2014)
Percutaneous coronary intervention (PCI) is a class I recommended therapy for both ST segment elevation myocardial infarction (STEMI) and unstable angina. Traditionally, PCI has been performed in large tertiary centers with on-site coronary bypass surgery programs. Over the past 10 to 15 years, “stand-alone” PCI programs have become more prevalent, particularly in the United States. Geographic, cultural, and financial challenges prohibit routine transfer to tertiary centers in a timely fashion. This article discusses the PCI program at Schneider Regional Medical Center.